Monumental heritage exposure to urban black carbon pollution. (December 2017) - Patrón, D.; Lyamani, H.; Titos, G.; Casquero-Vera, J.A.; Cardell, C.; Močnik, G.; Alados-Arboledas, L.; Olmo, F.J.
Abstract: In this study, aerosol light-absorption measurements obtained at three sites during a winter campaign were used to analyse and identify the major sources of Black Carbon (BC) particles in and around the Alhambra monument, a UNESCO World Heritage Site that receives over 2 million visitors per year. The Conditional Bivariate Probability Function and the Aethalometer model were employed to identify the main sources of BC particles and to estimate the contributions of biomass burning and fossil fuel emissions to the total Equivalent Black Carbon (EBC) concentrations over the monumental complex. Unexpected high levels of EBC were found at the Alhambra, comparable to those measured in relatively polluted European urban areas during winter. EBC concentrations above 3.0 μg/m 3, which are associated with unacceptable levels of soiling and negative public reactions, were observed at Alhambra monument on 13 days from 12 October 2015 to 29 February 2016, which can pose a risk to its long-term conservation and may cause negative social and economic impacts. It was found that road traffic emissions from the nearby urban area and access road to the Alhambra were the main sources of BC particles over the monument. However, biomass burning emissions were found to have very small impact on EBC concentrations at the Alhambra. The highest EBC concentrations were observed during an extended stagnant episode associated with persistent high-pressure systems, reflecting the large impact that can have these synoptic conditions on BC over the Alhambra. Graphical abstract: Highlights: BC monitoring in and near monument is essential for preventive conservation strategy. Unexpected high levels of BC were found inside and around the Alhambra monument. Road traffic emissions from the nearby urban area were the main source of BC. Contribution of biomass burning from the nearby rural areas was found. Stagnant weather conditions have a large impact on BC at the Alhambra.